TAFSIR ILMI MUKJIZAT AL-QUR’AN TENTANG ASTROFISIKA - Hasiolan Nasution (TAFAKKUR : Jurnal Ilmu Al-Qur'an dan Tafsir, 2024)
This article aims to express the Koran's views on astrophysics, one of the fields of science that studies the properties of physical phenomena and astronomical objects in the Universe. Some of Allah's verses are written and some are implied. The Qur'an is the written verse of Allah while the universe is the written verse of Allah. Because both are verses from Allah, there should be no conflict between the two because they both come from Allah SWT. This effort was carried out using qualitative methods and combining them with thematic interpretation methods. So it was found that the Koran talks a lot about written verses such as the sky, light, sun, moon, stars, black holes, and life outside the earth.